25.5k views
21 votes
Using ƒ(x) = 2x + 7 and g(x) = x − 3, find ƒ(g(x)).

Using ƒ(x) = 2x + 7 and g(x) = x − 3, find ƒ(g(x)).-example-1
User Alla
by
5.1k points

1 Answer

11 votes

Answer:

We get
\mathbf{f(g(x))=2x+1}

Option A is correct answer.

Explanation:

We are given:


f(x) = 2x + 7 \\g(x) = x - 3

We need to find f(g(x))

f(g(x)) can be found by putting x in f(x) equal to g(x)

Now, finding f(g(x))


f(x)=2x+7\\Put\:x=x-3\\f(g(x))=2(x-3)+7\\f(g(x))=2x-6+7\\f(g(x))=2x+1

So, we get
\mathbf{f(g(x))=2x+1}

Option A is correct answer.

User Flashspys
by
5.3k points